(untitled) (Medical Forum Monthly, 2022)
ABSTRACT Objective: To find a correlation between B-line score on lung ultrasound and fluid overload by clinical examination among CKD patients. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Nephrology, Sir Ganga Ram Hospital, Lahore from 20th October 2020 to 20th April 2021. Materials and Methods: Eighty seven patients meeting the inclusion criteria were enrolled. Clinical assessment for hypervolemia was done at the bedside and recorded. Lung ultrasound for B-line scoring was done for patients who fulfilled inclusion criteria. The lateral and anterior chest was checked sonographically from 2nd to 4th intercostal spaces on the left side and right-sided 2ndto5thintercostal spaces, at parasternal to mid-axillary lines (total 28 scanning sites). At these positions, the visible B-lines were counted, and scoring was done. Results: The mean age of the patients was 49.85±15.913 years, 46(52.87%) patients were male, and 41(47.13%) patients were females. There was a weak positive relationship identified between the B-line final score and fluid overload on clinical assessment i.e., r=0.356 (p<0.05). Conclusion: B-lines detected on lung ultrasonography have a weak positive relationship with the severity of volume overload among chronic kidney disease patients.